(untitled) (World Economics and Finance Bulletin, 2024)
This article analyzes the most effective way of developing the country’s innovative activity in regulating the activities of business entities in the conditions of modernization of the economy. In addition, the practice of innovation in the industry and in the Republic of Karakalpakstan was studied. Investment funds and venture funds are proposed as a financial mechanism for the regulation of business entities.